Aesthetic Reconstruction with Gingival Depigmentation: Rekonstruksi Estetika dengan Depigmentasi Gingiva - Zulfa, Liana (TALENTA, 2022)
Currently, there is an increase in the demand for aesthetics, which includes the need for a beautiful appearance. Gingival hyperpigmentation is an extremely disturbing aesthetic problem caused by melanin deposition of melanocytes in the basal and suprabasal layers of the epithelium. The color of the pigment can range from pale to dark brown or black, depending on the amount and distribution in the tissue. Gingival depigmentation therapy is a periodontal plastic surgery method that can provide patients with good outcomes. A 21-year-old female complained of having brown front gums and an unsettling appearance. The patient does not smoke, has allergies to drugs and food, or suffers from systemic disease. The depigmentation process was conducted using number15 scalpels, and the gingival contour was created before irrigation utilizing Kirkland. Furthermore, a periodontal pack was used to cover the surgical site, and there were no complaints during the postoperative follow-up visit.